1999
DOI: 10.1007/s002490050213
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of normal and cancerous human bladder cells studied by scanning force microscopy

Abstract: Scanning force microscopy was used for the determination of the elastic properties of living cells in their culture conditions. The studies were carried out on human epithelial cells. Two similar lines of normal cells (Hu609 and HCV29) and three cancerous ones (Hu456, T24, BC3726) were measured using the scanning force microscope in order to collect the force versus indentation curves. The BC3726 line originates from the HCV29 cell line which was transformed by the v-ras oncogene. To evaluate their elastic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
468
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(524 citation statements)
references
References 17 publications
31
468
1
2
Order By: Relevance
“…Comparison of the elastic properties of normal human epithelial cell lines (Hu609 and HCV29) and three cancerous ones (Hu456, T24, BC3726) showed that healthy cells have a Young's modulus of about one order of magnitude higher than cancer cells [932]. Addition of chitosan lead to an increase of stiffness of the cancer cells, whilst the non-malignant cells were not influenced by chitosan.…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…Comparison of the elastic properties of normal human epithelial cell lines (Hu609 and HCV29) and three cancerous ones (Hu456, T24, BC3726) showed that healthy cells have a Young's modulus of about one order of magnitude higher than cancer cells [932]. Addition of chitosan lead to an increase of stiffness of the cancer cells, whilst the non-malignant cells were not influenced by chitosan.…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…Importantly, they mostly fall within the range (10 4 , 10 6 ) Hz, an interval compatible with LITUS, which is already widely employed for medical applications. Peak frequency values outside this interval are found for the sole cases associated with extreme limit situations, that is, both when the cells behave as fluid-like (Maxwell) viscoelastic materials and exhibit the bladder cells [29] kidney cells [32] breast cells [30] prostate cells [30] thyroid cells [33] mouse ovarian epithelia [34] breast cells [35] prostate cells [36] bladder cells [29] breast cells [28] breast cells [26] cells of the lung [26] Figure 6. Bar chart with a synopsis of the theoretically derived in-frequency responses of healthy and cancer cells whose mechanical properties have been experimentally measured: the histograms compare peak frequencies for each tumour and normal cell line pair examined, by averaging over all the results obtained from the six viscoelastic schemes used.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 99%
“…This implies that the physical measurements generally can be strongly dependent on the technique used and, as a consequence, quantitative estimations may cover wide ranges. Several experimental tests [26][27][28][29][30][31][32][33][34][35][36]53] have in fact shown that Young's modulus of the cytoplasm of different (healthy and cancer) cell lines can oscillate from about 100 Pa to 10 kPa. Also, the size of the cell nucleus is of the order of a few micrometres and may depend on the cell size [54].…”
Section: Sensitivity Analyses: Qualitative Insights Into and The Resomentioning
confidence: 99%
“…For this purpose, slides were identified in which the slice level was oriented approximately in parallel to the hepatocyte sheets (allowing the identification of hepatocyte columns and sinusoids over at least 10 subsequent hepatocytes) and the shape of foci was photographically documented under a light microscope. Pa 450 (300-1000) Davidson et al (1995) and Lekka et al (1999) Sinusoids Young's modulus A Results from quantitative analysis of confocal laser scanning micrographs. B value assumed.…”
Section: Liver Tumor Initiation and Tissue Analysismentioning
confidence: 99%